2008
DOI: 10.1007/s11095-008-9572-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential Oral Delivery of 7-Ethyl-10-Hydroxy-Camptothecin (SN-38) using Poly(amidoamine) Dendrimers

Abstract: Purpose-To investigate potential application of poly(amidoamine) (PAMAM) dendrimers for improving the delivery of SN-38.Methods-Complexes of SN-38 with generation 4 amine terminated PAMAM dendrimers were synthesized with varying amounts of drug. Stability of the complexes as well as influence of complexation on permeability across and cellular uptake by Caco-2 cells was evaluated.Results-The complexes were stable at pH 7.4 and drug was released at pH 5. A tenfold increase in permeability and more than hundredf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 25 publications
2
62
0
Order By: Relevance
“…Initially, SN-38 was complexed to PAMAM G4.0-NH 2 , and its permeability was assessed across Caco-2 monolayers. 59 The results indicated that PAMAM G4.0-NH 2 -SN-38 conjugate showed up to 10-fold higher permeability and 100-fold higher uptake than free SN-38. However, the complex was not stable under acidic conditions.…”
Section: Pamam-dendrimer-drug Conjugates and Complexes For Oral Deliverymentioning
confidence: 93%
See 1 more Smart Citation
“…Initially, SN-38 was complexed to PAMAM G4.0-NH 2 , and its permeability was assessed across Caco-2 monolayers. 59 The results indicated that PAMAM G4.0-NH 2 -SN-38 conjugate showed up to 10-fold higher permeability and 100-fold higher uptake than free SN-38. However, the complex was not stable under acidic conditions.…”
Section: Pamam-dendrimer-drug Conjugates and Complexes For Oral Deliverymentioning
confidence: 93%
“…However, the complex was not stable under acidic conditions. 59 In a follow-up study, SN-38 was covalently conjugated to PAMAM G3.5-COOH with glycine and b-alanine spacers and their transepithelial transport was evaluated on Caco-2 cell monolayers. 60 G3.5-Gly-SN38 at 100 mM and G3.5-bala-SN38 at 10 mM and 100 mM showed a statistically significant increase in apical to basolateral SN-38 flux relative to free SN-38 (p < 0 .001).…”
Section: Pamam-dendrimer-drug Conjugates and Complexes For Oral Deliverymentioning
confidence: 99%
“…Conjugation or complexation of therapeutics with poor solubility and low permeability (e.g. Biopharmaceutics Classification System Class 3 and 4 compounds) to water-soluble dendrimers that can permeate the epithelial layer of the gut has the potential to render these drugs orally bioavailable (12)(13)(14). Oral drug administration has many advantages, including the convenience of at-home administration, reduction of direct and indirect costs, and a more flexible dosing regimen, resulting in higher patient compliance and a lower burden on hospitals and the healthcare system (15).…”
Section: Introductionmentioning
confidence: 99%
“…However, dose-limiting side effects caused by the water-solubilizing functionalities include severe to life-threatening diarrhea and myelosuppression [171,172]. Consequently, smart delivery vehicles for camptothecins that can reduce side effects while enhancing potency are of particular interest [23,74,[173][174][175]. The work of Grinstaff and coworkers using polyester dendrimers represents an interesting example [101].…”
Section: Methodsmentioning
confidence: 99%
“…Often drugs are not compatible with use of the protein transporter system that is designed to pass nutrients. The oral route using dendrimers looks very promising especially with anticancer and antihypertensive drugs [23,[71][72][73][74][75].…”
Section: Oral Drug Deliverymentioning
confidence: 99%